2013
DOI: 10.1155/2013/713061
|View full text |Cite
|
Sign up to set email alerts
|

Cystoid Macular Edema Induced by Low Doses of Nicotinic Acid

Abstract: Cystoid macular edema (CME) is a condition that involves the macula, causing painless vision loss. In this paper, we report a case of niacin-induced bilateral cystoid macular edema (CME) in a middle-age woman taking low dose of niacin (18 mg of nicotinic acid). Optical coherence tomography (OCT) showed retinal thickening and cystoid spaces in both eyes, whereas fluorescein angiography (FA; HRA 2, Heidelberg Engineering) revealed the absence of fluorescein leakage also in later phases. Four weeks after disconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
1
9
0
5
Order By: Relevance
“…Niacin is closely related to lipid metabolism, amino acid and protein metabolism in animals (Hansen et al, 2015, Luo et al, 2017. It has a positive effect on increasing high-density lipoprotein cholesterol (HDL-C) and decreasing triglycerides (TG) (Domanico et al, 2015, Le et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Niacin is closely related to lipid metabolism, amino acid and protein metabolism in animals (Hansen et al, 2015, Luo et al, 2017. It has a positive effect on increasing high-density lipoprotein cholesterol (HDL-C) and decreasing triglycerides (TG) (Domanico et al, 2015, Le et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced CME can be caused by various drugs such as taxanes, 4 acitretin 5 , tamoxifen, 6 niacin 7 , interferon, fingolimod, 8 prostaglandin, epinephrine, and timolol among others. 9 However, systemic anti-histamines- or anti-histamine eye drops-induced CME has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 While for drug-induced CME, several papers have reported that CME was not observed to be associated with leakage on fluorescein angiography. 12 , 13 , 14 , 15 Therefore, the mechanisms of drug-induced CME may differ from those of microvascular occlusion or inflammatory disease. The characteristics of drug-induced CME 6 are: (1) often bilateral, (2) no leakage on fluorescence fundus angiography (FFA), (3) a larger cystic space in the outer rather than the inner layer of the retina on OCT scans, and (4) spontaneous resolution and improvement of visual acuity after discontinuation of the causative drug.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Niasin-Nikotinik Asit Niasin (nikotinik asit) hiperkolesterolemi tedavisinde oral olarak kullanılan bir vitamin preparatıdır. [21] Plazma apolipoprotein A ve B seviyelerini düşürerek plazma HDL, LDL ve VLDL düzeylerini azaltmakta ve trigliserid sentezini baskılamaktadır. [22] Niasinin oküler yan etkilerinin doz bağımlı ve geri dönüşümlü olduğu, yüksek dozda niasin kullananlarda 1-36 ay sonra makulopati geliştiği bildirilmektedir.…”
Section: Epinefrinunclassified
“…[21] Plazma apolipoprotein A ve B seviyelerini düşürerek plazma HDL, LDL ve VLDL düzeylerini azaltmakta ve trigliserid sentezini baskılamaktadır. [22] Niasinin oküler yan etkilerinin doz bağımlı ve geri dönüşümlü olduğu, yüksek dozda niasin kullananlarda 1-36 ay sonra makulopati geliştiği bildirilmektedir. [21] Günde 1.5 gramın üzerinde niasin kullanan hastalarda KMÖ riskinin arttığı saptanmıştır.…”
Section: Epinefrinunclassified